Effect of Next Nearest Neighbor Interaction on Thermodynamic Properties of Ultrathin Magnetic Films - Nguyen, Tu Niem (H. : ĐHQGHN, 2019)
This work studies on the thermodynamic properties of the ultra-thin magnetic films within the framework of a transverse Ising model. Equations for free energy, entropy and specific heat of spin system are obtained by using the mean field approximation. We also analyze the effect of the next nearest neighbor interaction on critical temperature, layer magnetization and specific heat of the thin films.